LOGISTICS DELIVERY APPLICATION FOR MEDICAL EQUIPMENT AT PT. MITRA FAJAR SELARAS BASED ON WEBSITE - Warno Warno; Taufiqqurrachman Taufiqqurrachman; Muhammad Ridho Santoso (LPPM YPITI, 2026)
Advances in computer-based technology is utilized by the company by making the computer as a tool to process data into a fast and accurate information so that the company can accelerate the completion of a job. In processing input usage and managing corporate data is also still see the status of goods shipped are still using Microsoft Word And Excel, but only implemented in the process of typing data and making tables, after the data is typed and then printed to be a report in the company. the system used today still poses a problem in the process of operation. The research method used is to conduct interviews, and literature studies in order for this study to obtain accurate data for the application of medical device delivery at PT. Mitra Fajar Selaras based Website can be built with existing information. By using the Waterfall method or waterfall. This Model proposes an approach to systematic and sequential Website development that starts from the level of system progress across analysis, design, code, testing and maintenance. This research is expected at PT. Mitra Fajar Selaras Shipping Logistics has been based on the website as an alternative medium in order to assist the company in the process of delivering information and data management quickly and accurately to support the process of delivering quality goods in monitoring and accelerating delivery distribution.